Amphiphilic hollow porous shell encapsulated Au@Pd bimetal nanoparticles for aerobic oxidation of alcohols in water1. Issue 78 (7th October 2015) - Zou, Houbing; Wang, Runwei; Dai, Jinyu; Wang, Yu; Wang, Xue; Zhang, Zongtao; Qiu, Shilun
<x xml:space="preserve">Abstract</x> Amphiphilic hollow porous shell encapsulated Au@Pd bimetal nanoparticles have been developed for application in aerobic oxidation of alcohols in water.